The CFIA model revised : the way forward for the brazilian international investment regime - Sachetim, Henrique Martins (2021)
In 2013, the Brazilian government approved its Cooperation and Facilitation Investment Agreement (CFIA) model. It has declared that the CFIA model integrates the most recent trends in investment policies, materializing the governments intention to build a new approach in the promotion and protection of investments. However, the CFIA model is only partially supported by academia and largely criticized by domestic and foreign investors and capital-exporting countries. The purpose of this study is to scrutinize the CFIA model to identify how it the balances States need for policy space and investors right for protection to propose the way forward for the Brazilian international investment regime. The CFIA model is evaluated holistically through its institutional design and main substantive and procedural provisions to give robustness to the investigation. Analyzing these intertwined elements combined determines the value of an investment framework, not the evaluation of its components in isolation. To successfully deal with the main apprehensions about the CFIA model, the stateof-art literature on ways to overcome the challenges faced by the international investment regime has served as a basis of assessment for elaborating a revised Brazilian regime. The study has also considered the criticism and lessons learned from the international and the Brazilian experiences with the traditional bilateral investment treaty (BIT) model, and the institutional choices and procedure and substantive disciplines found in the European Union (EU) model of investment treaty and the United States-Mexico-Canada Free Trade Agreement, attempting to understand the reasons for their institutional design, and drawing analogies and distinctions between the models and other international regulations. The EU and the United States are among the leading players searching for ways to improve the international investment regimes structure, disciplines, and rules. This study concludes that the Brazilian treaty-language fails to provide legal certainty and the model has overshot in its effort towards correcting the unbalance between States need for policy space and investors right for protection in the traditional BIT model. The study also presents several intertwined proposals for systemic reform of the Brazilian international investment regime. The proposals can contribute to constructing a renewed Brazilian regime that fosters the political and legal stability and predictability necessary for domestic and foreign investors to engage in new or additional investments while safeguarding the pursuit of competing public policy concerns. They enhance democratic legitimacy, fairness, and the rule of law, improve resource allocation efficiency, reduce diplomatic confrontation and protect fundamental and human rights, recognizing investment treaty as a tool rather than an obstacle to sustainable development. Several proposals can be easily adopted by the Executive and lately approved by Congress. However, to strengthen protection for investors while safeguarding public policy space, the Brazilian government must design its reformed regime transparently and inclusively to ensure the necessary support for its adoption and later entry into force.